2017
DOI: 10.1016/j.bbalip.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids in mitochondria

Abstract: Sphingolipids are bioactive lipids found in cell membranes that exert a critical role in signal transduction. In recent years, it has become apparent that sphingolipids participate in growth, senescence, differentiation and apoptosis. The anabolism and catabolism of sphingolipids occurs in discrete subcellular locations and consist of a strictly regulated and interconnected network, with ceramide as the central hub. Altered sphingolipid metabolism is linked to several human diseases. Hence, an advanced knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 149 publications
0
83
1
2
Order By: Relevance
“…Sphingolipids are building blocks of the mitochondrial membranes, where they exert various structural and functionrelated tasks. 23,32 Hence, their production can be seen as a proxy for the generation of mitochondria at early time points. Our results therefore suggest that by producing mitochondria, cardiomyocyte differentiation lays the foundation for enabling beta-oxidation of fatty acids, which indeed was detected at later stages of differentiation by our GO analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids are building blocks of the mitochondrial membranes, where they exert various structural and functionrelated tasks. 23,32 Hence, their production can be seen as a proxy for the generation of mitochondria at early time points. Our results therefore suggest that by producing mitochondria, cardiomyocyte differentiation lays the foundation for enabling beta-oxidation of fatty acids, which indeed was detected at later stages of differentiation by our GO analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These changes affect both the arrangement and properties of the membrane proteins, such as receptors, transporters, and signaling complexes that will transmit the signal further down the line (Edmond et al, 2015; Lockshon et al, 2012). In addition, both short- and long-chain ceramides were able to form stable ceramide channels in planar membranes in vitro, though the experimental evidence for this process in vivo is still missing (Hernandez-Corbacho, Salama, Canals, Senkal, & Obeid, 2017; Siskind & Colombini, 2000). Alternatively, ceramide elevation resulting from treatment of A549 cells with methotrexate caused ER (endoplasmic reticulum) membrane aggregation leading to apoptosis (Fekry, Esmaeilniakooshkghazi, Krupenko, & Krupenko, 2016).…”
Section: Ceramide Signaling: Mechanismsmentioning
confidence: 99%
“…Sphingolipid metabolism is vitally important for the regulation of cell proliferation, aging and differentiation. 55,56 Furthermore, VEGF has the strongest promoting effect on the growth of endothelial cells and is one of the most important cytokines for promoting angiogenesis. Grosjean et al 57 have shown that VEGF could protect vascular endothelial cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%